A new Atractides Koch (Acari: Hydrachnidia, Hygrobatidae) species from southwestern Turkey - Gülle, Pinar; Gülle İskender; Boyaci, Yunus Ömer (Zootaxa, 2015)
Description of a new Atractides species, Atractides reinhardi n. sp., from Burdur Province of Turkey is given.